Correlation of Compressive and Flexural Strengths of Concrete Affected by Cement Type and Admixture - Masdar Helmi; I M.A.K. Salain; Chatarina Niken; Elfa Damayanti (Jurnal Rekayasa Lampung, 2026)
Compressive strength (fc’) and flexural strength (fs) are key mechanical properties used in concrete design, and their correlation has been investigated by many researchers. However, existing models often provide limited accuracy because they do not consider differences in cement type and chemical admixture. This study investigates the effects of cement type, curing age, and admixture on compressive and flexural strengths and develops an empirical correlation between fc’ and fs. Experimental testing was performed using Portland Composite Cement (PCC) and Ordinary Portland Cement (OPC), with and without admixture. Cylinder specimens (150 × 300 mm) were tested for compressive strength, while beam specimens (150 × 150 × 600 mm) were tested for flexural strength at 7 and 28 days. Admixture increased compressive strength by up to 48.4% and flexural strength by up to 19.6% compared with conventional concrete. The best correlation was obtained using the power regression model fs = 0.3209(fc’)^0.8207, with a coefficient of determination R² = 0.8572, exceeding the predictive performance of ACI 318 equations. The proposed model provides a more accurate and reliable prediction of the compressive–flexural strength relationship for the concrete mixtures evaluated in this study.